Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1136/jech.2009.102319
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a school-based intervention in eating habits and physical activity in school children: the AVall study

Abstract: BackgroundObesity has become a global public health problem, which also affects children. It has been proposed that the educational interventions during childhood could be a key strategy in the prevention of obesity.ObjectiveTo evaluate the efficacy of an intervention on food habits and physical activity in school children.MethodsA 2-year cluster-randomised prospective study with two parallel arms was used to evaluate an intervention programme in children in their first year of primary schooling (5–6 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
0
35

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(139 citation statements)
references
References 19 publications
4
98
0
35
Order By: Relevance
“…In agreement with our findings, Llargues and colleagues (14) reported that educational intervention in primary students was not significantly effective in changing their eating habits but the height was increased more in the intervention group compared to the control group.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…In agreement with our findings, Llargues and colleagues (14) reported that educational intervention in primary students was not significantly effective in changing their eating habits but the height was increased more in the intervention group compared to the control group.…”
supporting
confidence: 82%
“…The trial was registered at IRCT as IRCT2014021613080N2. Sample Size: Sample size was estimated based on a similar study (α=0.05, β=0.2, d=1.9 and δ=2.5) (14). The study was conducted on 221 students but 171 children (83 in the case and 88 in the control group) with the age range of 9.5 to 10.5 years were eligible to be included in data analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, en cuanto a métodos, el consumo de alimentos, se recogió con una frecuencia cualitativa de consumo, por lo que el cambio se midió en patrones de alimentación y no en forma cuantitativa, al respecto, otros estudios han aplicado este método de consumo de alimentos para evaluar la efectividad de la intervención (13,28) . Asimismo, el nivel de actividad física se hizo con cuestionario, lo cual torna subjetiva, en parte, la determinación, al respecto, cabe precisar que este instrumento ha sido validado con acelerómetros triaxiales para determinar su utilidad, varios estudios han evaluado el efecto de una intervención con cuestionarios de actividad física, considerando que la actividad física en escolares tiene un patrón regular (11,13,30) . En conclusión, el estudio muestra que al primer año de intervención "Como Jugando" no tuvo impacto sobre el IMC; sin embargo, tiene efecto atribuible sobre el aumento de conocimientos en nutrición, reduce la probabilidad de tener un nivel malo de actividad física y mantiene o aumenta la frecuencia adecuada del consumo de frutas, agua sin azúcar y mantiene un consumo menor a dos veces por semana de jugos envasados y galletas dulces y saladas.…”
Section: Referencias Bibliográficasunclassified
“…Research evidence has shown that it is diffi cult to treat obesity in adult life through changes in lifestyle rather than doing so in early childhood/youth years. 8 Obesity prevention needs to be targeted at children who are under 11 years of age. Parents' involvement is a crucial component for any school-based intervention.…”
Section: Overview Of Obesity Prevention (Intervention) Studiesmentioning
confidence: 99%